Human Resource Management Strategy in Adapting to Work System Changes at Perum BULOG - P, Maysius; Suyuthi, Nurmadhani Fitri; Ipmawan, Ipmawan; Astriya, Delly (Journal La Bisecoman, 2024)
The given research examines the extent to which the system of human resource management (HRM) enables the adaptation of employees to systemic changes in work in the state enterprise Perum BULOG, Bone Branch Office which is faced with reforms in its functioning organization. Following quantitative research design and census sampling pool consisting of 21 employees, the paper assesses the effect of four HRM strategies, which include training and development, communication, performance management and employee involvement. The data transacted using a structured questionnaire and analyzed using multiple linear regression. The findings suggest that training and development, the communication and employee involvement have a statistically significant impact on adaption of the employees, but the performance management does not. This evidence indicates that employee adaptation cannot occur through the simple effect of organizational change but a developed reaction developed through critical HR facilitating tactics. This paper thus notes that the contribution of the employees to the change processes, continuity of capacity-building opportunities, and free and two-way communication would ensure alignment and engagement. In addition to this, it shows that performance systems limited to evaluation and not involving developmental feedback is unable to help adaptation. Since 60 percent of the variance in adaptation was attributed to the chosen HRM strategies, the research confirms the focus of HR in the transformation of the public sector.